THE USE OF PRONUNCIATION SOFTWARE TO IMPROVE STUDENTSâ PRONUNCIATION - Muna, Faizul (ENCOUNTER, 2012)
The pronunciation software is medium to improve studentsâ pronunciation that provides fun and interesting activity. The study is aimed to find out the implementation of teaching pronunciation using pronunciation software and the improvement of studentsâ pronunciation after being taught through using pronunciation software is. This study is Classroom action research with the subject of 39 students of SMA Islam Al- Hikmah Mayong Jepara in the academic year of 2011/2012, 12 boys and 27 girls. The researcher collected the data from the observation and tests. There are three cycles; teacher gives different treatment in every cycle. The result shows that there was a significant difference of the students achievement between the results scoring in every cycle was increasing. It was found that teaching pronunciation using pronunciation software is effective and helpful in improving studentsâ ability of pronunciation skill. As the result in the tests that the studentsâ improvement during the treatment through pronunciation software, the average of the tests scores increased from 69.1025 in the pre cycle, it was becoming 77.5641 in the first cycle, it was becoming 80.1282 in the second cycle, and then it was becoming 87.4358 in the third cycle.